The nature of the relationship between Al-Bakr and Saddam, from 1968 to 1979. - Rese. Rehab Abbas Nahi Kaeid Al-Zwaini; Dr. Talib Muhaibis Al-Waeli (Journal of College of Education, 2024)
The nature of the relationship between Al-Bakr and Saddam, starting from 1968 until 1979. Saddam Hussein was mocking all the roles and circumstances that occurred in Iraq after 1968, in order to enhance his position and strengthen his position in the government and the party, as Saddam, at the beginning of Baathist rule, followed a cunning policy in dealing with the cadres of the party and the state. He pretended to be humble, generous, and quick to meet the needs of his companions in need. From those who followed the relationship between Al-Bakr and Saddam, there were notes that the two tried to hide, but to the observer they gave the impression of the existence of a dispute. One of the important issues was Al-Bakr stepping down from power by force, and this is conclusive evidence of the bad relationship between them. The two sides, and here the page of al-Bakr turned and the page of the bloody clash began.
Keywords: the relationship, Al-baker, Saddam.